Cigarette Smoke Induced Lung Barrier Dysfunction, EMT, and Tissue Remodeling: A Possible Link between COPD and Lung Cancer. (24th June 2019) - Hou, Wei; Hu, Siyi; Li, Chunyan; Ma, Hanbin; Wang, Qi; Meng, Guangping; Guo, Tingting; Zhang, Jie
Abstract : Chronic obstructive pulmonary disease (COPD) and lung cancer, closely related to smoking, are major lung diseases affecting millions of individuals worldwide. The generated gas mixture of smoking is proved to contain about 4, 500 components such as carbon monoxide, nicotine, oxidants, fine particulate matter, and aldehydes. These components were considered to be the principle factor driving the pathogenesis and progression of pulmonary disease. A large proportion of lung cancer patients showed a history of COPD, which demonstrated that there might be a close relationship between COPD and lung cancer. In the early stages of smoking, lung barrier provoked protective response and DNA repair are likely to suppress these changes to a certain extent. In the presence of long-term smoking exposure, these mechanisms seem to be malfunctioned and lead to disease progression. The infiltration of inflammatory cells to mucosa, submucosa, and glandular tissue caused by inhaled cigarette smoke is responsible for the destruction of matrix, blood supply shortage, and epithelial cell death. Conversely, cancer cells have the capacity to modulate the proliferation of epithelial cells and produce of new vascular networks. Comprehension understanding of mechanisms responsible for both pathologies is necessary for the prevention and treatment of COPD and lung cancer. In this review, we will summarize related articles and give a glance of possible mechanism between cigarette smoking induced COPD and lung cancer.